High prevalence of the hotspot complement factor I p.Ile357Met pathogenic variant in Tunisian atypical hemolytic uremic syndrome patients: report of three new cases and review of the literature - Tajouri, Asma; Ayadi, Imen; BenBrahim, Rimeh; Mami, Ikram; Boussetta, Abir; Jlajla, Hend; Zerzeri, Yousr; Arbi Sassi, Haifa; Ben Sassi, Jamila; Sahli, Hela; Laadhar, Lilia; Gargah, Tahar; et al. (Frontiers in Immunology, 2025)
IntroductionAtypical Hemolytic Uremic Syndrome (aHUS) is the prototype of renal diseases secondary to dysregulation of the alternative complement pathway. Our previous studies demonstrated that factor I deficiency appears to be common in Tunisian aHUS patients with the recurrence of a rare variant c.1071T>G (p.Ile357Met) localized within exon 10 of the Complement Factor I (CFI) gene. Data in the literature have demonstrated that this variant has a pathogenic effect affecting factor I synthesis and function. The recurrence of this variant in the Tunisian cohort led us to suggest that it could be characteristic of the Tunisian population.MethodsIn this context, we conducted the current study which included 8 adults and three children with suspected aHUS and decreased factor I levels, as well as one relative. We performed molecular investigation by targeting specifically the p.Ile357Met mutation of the CFI gene by direct sequencing.Results and discussionInterestingly, our results showed that the p.Ile357Met mutation was detected in 3 patients out of 11 (two children and one adult) as well as in one relative. Taking into account the high frequency of this pathogenic variant we could confirm that this latter is a hotspot which could be specific to our population. Thus, it would be interesting to look specifically for this variant in any Tunisian aHUS patient with decreased complement factor I level.